Pelatihan Pemanfaatan Aplikasi Pembelajaran Berbasis Game Kahoot Di SMA Islam Terpadu Misykat Al Anwar - Zuhriyah, Fatimatuz; Susilowati, Lina; Munawaroh, Munawaroh (CV. IRA PUBLISHING, 2024)
The determinant of a teacher's learning success lies in the teaching process, which is able to attract student's interest so that they do not get bored quickly while learning by utilizing learning media. Misykat Al Anwar Integrated Islamic High School, in improving the quality of learning and teacher skills, held an agenda, namely The Great and Innovative Teacher Movement. These activities do not only focus on a teacher's abilities, especially game-based learning media, namely Kahoot! Kahoot is a game-based learning media that teachers can use in the teaching and learning process in class to create a more interactive atmosphere! The target of this community service activity is 23 teachers. This activity aims to improve teachers' skills in using the Kahoot application. The method of implementing this activity is in the form of lectures, discussions, practice, and assignments. The results of this service activity are as follows: (1) Teachers are familiar with the Kahoot application for creating online quizzes, and (2) teachers' skills in using the Kahoot application are improved.